A case of mediastinal emphysema caused by root canal treatment using Er: YAG laser. Issue 2 (March 2020) - Kuromatsu, Yuki; Nakano, Hiroyuki; Inoue, Kazuya; Ogura, Ayano; Omori, Michi; Nakajima, Yoichiro; Ueno, Takaaki
Abstract: Subcutaneous emphysema is often reported to develop because of dental treatment. We report a case of cervicofacial, subcutaneous, and mediastinal emphysema caused by dental laser treatment. The patient consulted our hospital complaining of swelling and pain across his both sides of the forehead, around the eye lid, from left cheek to the neck. On computed tomography, low absorption images indicative of air infiltration were found scattered from the forehead and left side of the face to the left side of the neck. We admitted the patient to monitor his airway, for bed rest, and to initiate prophylactic intravenous antibiotic therapy. Consequently, 6 days after the dental laser treatment, the patient's cervicofacial swelling disappeared and the subcutaneous crepitus was almost undetectable. In this case, although secondary infection such as mediastinitis did not develop, it is necessary to consider hospitalization of patients who developed mediastinal emphysema after laser treatment for incision of abscess.